Perspectives and Expertise in Establishing a Therapeutic Drug Monitoring Programme for Challenging Childhood Cancer Patient Populations - Barnett, Shelby; Holden, Victoria; Campbell-Hewson, Quentin; Veal, Gareth J. (Frontiers in Oncology, 2022)
The utility of Therapeutic Drug Monitoring (TDM) in the setting of childhood cancer is a largely underused tool, despite the fact that treatment commonly involves administration of cytotoxic chemotherapeutics. While it is encouraging that modern advances in chemotherapy have been transformative for the outcomes of children diagnosed with cancer, this has come at the cost of an elevated risk of life-changing long-term morbidity and late effects. This concern can limit the intensity at which these drugs are used. Widely used chemotherapeutics exhibit marked inter-patient variability in drug exposures following standard dosing, with fine margins between exposures resulting in toxicity and those resulting in potentially suboptimal efficacy, thereby fulfilling criteria widely accepted as fundamental for utilising TDM treatment approaches. Over the past decade in the UK, the paediatric oncology community has increasingly embraced the potential benefits of utilising TDM approaches for particularly challenging patient groups, including neonates and infants, anephric patients and those receiving high dose chemotherapy regimens. This has been driven by a desire from paediatric oncologists to have access to clinical pharmacology information to support dosing decisions being made. This provides clinicians with the potential to modify doses between cycles of treatment based on a comprehensive set of clinical information, with individual patient drug exposures being used alongside clinical response and tolerability data to inform dosing for subsequent cycles. The current article provides an overview of recent experiences of conducting TDM in a childhood cancer setting, from the perspectives of the clinicians, scientists and pharmacists implementing TDM-based dosing recommendations.